Trends, Thematic Maps, and Collaboration Networks in Singapore's Multicultural Counseling Research: A Bibliometric Review - Faizal Ramley; Muhammad Ilham Bakhtiar; Rahmaeni; A. Agustan Arifin; Idriani Idris; Hadryanti (International Journal of Multicultural Counseling and Development, 2026)
The purpose of this study is to determine (1) the development trends of multicultural counseling research analysis in Singapore based on bibliometrics; (2) Main themes, study focus, and research trend topics in multicultural counseling studies in Singapore; (3) Research collaboration in multicultural counseling studies in Singapore. The study uses bibliometric analysis with data from OpenAlex totaling 600 manuscripts for the period 2020–2026 using the search query TITLE-ABS-KEY ("multicultural counseling" OR "cultural counseling" OR "cross-cultural counseling" OR "culturally responsive counseling") AND TITLE-ABS-KEY (Singapore) analyzed using Biblioshiny and R.Studio. The results show that the annual publication trend is fluctuating but tends to increase, with peak productivity in 2025, predominantly published in the Journal of Multicultural Counseling and Development. Thematic map and keyword analysis found psychology, multiculturalism, and pedagogy as the main basis of the research. However, this academic landscape faces structural challenges in the form of fragmented collaboration between authors and a heavy reliance on the Singapore–United States transnational research axis.